High-performance flame-retardant adhesive, preparation method thereof and flame-retardant cotton paper double-sided tape
By using modified flame retardant and polymer materials, high-performance flame retardant adhesives are prepared, which solves the problem of degradation of bonding performance caused by the improvement of flame retardant performance in the prior art, and realizes the flame retardant cotton paper double The good initial adhesive, peeling force, retention force and flame retardant properties of the surface tape are suitable for bonding of automotive interior materials.
Patent Information
- Application Number
- CN202411360724.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
When existing flame retardant cotton paper double-sided tapes improve flame retardant performance, they often lead to degradation of the initial adhesive performance and bonding performance of the glue, especially under high temperature conditions, which is difficult to meet the high level of automotive interior materials. Bonding requirements.
High-efficiency flame retardants such as modified ammonium polyphosphate or modified aluminium diethyl hypophosphate can be used to improve the dispersion and bonding properties of the flame retardants through surface grafting and crosslinking treatment, and combine polymers and adhesive bonding. Resin, high-performance flame retardant adhesive is prepared, used to prepare flame retardant tissue double-sided tape.
The flame-retardant cotton paper double-sided tape has achieved good initial adhesive performance, high peeling force, high retention force and good flame retardant performance. It can hang 0.5kg weights at 60℃*95% without falling, and sticking them. After connecting to the PP material, the overall flame of the material is extinguished before reaching the first marking line, meeting the bonding needs of automobile interior materials.
Smart Images

Figure BDA0005064874750000171 
Figure BDA0005064874750000181
Abstract
Description
Technical Field
[0001] The invention relates to the field of flame retardant adhesive materials, and in particular to a high-performance flame retardant adhesive, a preparation method thereof and a flame retardant cotton paper double-sided tape. Background Art
[0002] As an essential tool for modern people to travel, cars are becoming more and more important to people’s safety while pursuing comfort and aesthetics. However, in recent years, car accidents are still frequent, causing casualties. Many domestic studies have shown that the main reason for the heavy losses is that after a car fire, the flame retardant performance of the car’s interior decoration materials is poor, especially the flame retardant grade of interior materials such as plastics and fabrics is too low, which contributes to the spread of the fire, thereby exacerbating the casualties and property losses of passengers.
[0003] As one of the materials for automobile interior decoration, car seat cushions are mostly made of polymer materials (plastics, fibers, leather, rubber, etc.) through multi-layer composite preparation. These materials are mostly fixed by pressure-sensitive adhesive bonding. Pressure-sensitive tape is a kind of pressure-sensitive adhesive, that is, it can quickly adhere to the surface when slight pressure is applied, with high processing efficiency. Pressure-sensitive adhesive can form a uniform adhesion layer on different types of substrates. Compared with other chemical adhesives, it has strong adhesion, is easy to use, and can cope with different conditions, such as temperature, humidity, etc. It has the advantages of environmental protection, non-toxicity, high cost performance, and adjustable viscosity. Among them, from the perspective of processability and conformability, cotton paper double-sided tape with cotton paper as the base material is widely used in the bonding of various automobile interior materials.
[0004] There are many kinds of materials for automobile interior decoration, such as polypropylene, polyethylene, polycarbonate, polyurethane foam, etc. On the one hand, most of these materials are flammable or combustible items. When burning, they have a large heat release rate, high calorific value, fast flame propagation speed, and are not easy to extinguish. Sometimes they also produce thick smoke and toxic gases, which are harmful to human health and the environment. On the other hand, for pressure-sensitive adhesives, due to the influence of factors such as low surface energy and rough surface of interior materials, these interior materials are difficult to bond, and higher requirements are placed on the bonding performance of pressure-sensitive adhesives.
[0005] Currently, most of the flame retardant cotton paper double-sided tapes on the market are prepared by adding flame retardants to pressure-sensitive glue to make flame retardant glue, and then coating the flame retardant cotton paper double-sided tape. However, in order to improve the flame retardant properties of the glue, flame retardants are added to the glue. However, the addition of flame retardants often leads to a decrease in the performance of the glue. For example, the initial adhesion performance becomes lower, which is not conducive to the adhesion of rough material surfaces; the decrease in the cohesive performance of the glue leads to the undesirable phenomenon of adhesion failure of the fabric after long-term aging, especially under high temperature conditions.
[0006] In view of the above problems, the present invention provides a flame retardant cotton paper double-sided pressure-sensitive adhesive tape for use in bonding automotive interior materials. While providing efficient bonding performance, it also has good flame retardant performance. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a high-performance flame-retardant adhesive, a preparation method thereof and a flame-retardant cotton paper double-sided tape in view of the deficiencies in the above-mentioned prior art.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, a high-performance flame-retardant adhesive is provided, characterized in that it comprises the following raw material components in parts by weight: 100 parts of a high molecular polymer, 40 to 80 parts by weight of a high-efficiency flame retardant, 5 to 50 parts by weight of a tackifying resin, 1 to 7 parts of a curing agent, and 60 to 100 parts by weight of a first solvent;
[0009] Wherein, the high-efficiency flame retardant is modified ammonium polyphosphate or modified diethyl aluminum hypophosphite.
[0010] Preferably, the modified ammonium polyphosphate is prepared by the following method:
[0011] 1-1) 50-200 g of ammonium polyphosphate passed through a 200 mesh sieve is heated and stirred at 220-260° C. for 20-80 min for activation, and then 5-20 g of melamine formaldehyde resin is added, and the temperature is maintained and stirred for 1-4 hours in a closed environment to obtain ammonium polyphosphate grafted with melamine formaldehyde resin;
[0012] 1-2) The melamine formaldehyde resin grafted ammonium polyphosphate prepared in step 1-1) is mixed with a methanol aqueous solution with a mass fraction of 6-24% in a mass ratio of 0.5-2:1-4, and then 20-50wt% of formalin solution is added in a ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde molar ratio = 0.5-2:1-4, and the mixture is stirred in a closed manner at 70-95° C. for 1-4 hours, filtered, washed with water, and the obtained filter cake is dried to obtain modified ammonium polyphosphate.
[0013] Preferably, the modified ammonium polyphosphate is prepared by the following method:
[0014] 1-1) 100 g of ammonium polyphosphate passed through a 200 mesh sieve was heated and stirred at 240° C. for 40 min for activation, and then 10 g of melamine formaldehyde resin was added, and the temperature was maintained and stirred for 2 hours in a closed environment to obtain ammonium polyphosphate grafted with melamine formaldehyde resin;
[0015] 1-2) The melamine formaldehyde resin grafted ammonium polyphosphate prepared in step 1-1) is mixed with a 12% methanol aqueous solution in a mass ratio of 1:2, and then a 37wt% formalin solution is added in a ratio of a molar ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde = 1:2, and the mixture is stirred in a closed manner at 85°C for 2 hours, filtered, washed with water, and the filter cake is dried at 70°C for 24 hours to obtain modified ammonium polyphosphate.
[0016] Preferably, the modified diethyl aluminum hypophosphite is prepared by the following method:
[0017] 1-1) 50-200 g of diethyl aluminum hypophosphite passed through a 200 mesh sieve is heated and stirred at 220-260° C. for 20-80 min for activation, and then 5-20 g of melamine formaldehyde resin is added, and the temperature is maintained and stirred for 1-4 hours in a closed environment to obtain diethyl aluminum hypophosphite grafted with melamine formaldehyde resin;
[0018] 1-2) The melamine formaldehyde resin grafted diethyl aluminum hypophosphite prepared in step 1-1) is mixed with a methanol aqueous solution with a mass fraction of 6-24% in a mass ratio of 0.5-2:1-4, and then 20-50wt% of formalin solution is added in a ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde molar ratio = 0.5-2:1-4, and the mixture is stirred in a closed manner at 70-95° C. for 1-4 hours, filtered, washed with water, and the obtained filter cake is dried to obtain modified diethyl aluminum hypophosphite.
[0019] Preferably, the modified diethyl aluminum hypophosphite is prepared by the following method:
[0020] 2-1) 100 g of diethylaluminum hypophosphite passed through a 200-mesh sieve was taken, heated and stirred at 240° C. for 40 min for activation, and then 10 g of melamine formaldehyde resin was added, and the temperature was maintained and stirred for 2 hours in a closed environment to obtain diethylaluminum hypophosphite grafted with melamine formaldehyde resin;
[0021] 1-2) The melamine formaldehyde resin grafted diethyl aluminum hypophosphite prepared in step 1-1) is mixed with a 12% methanol aqueous solution in a mass ratio of 1:2, and then a 37wt% formalin solution is added in a ratio of 1:2 of the molar ratio of ammonium polyphosphate grafted with melamine formaldehyde resin: formaldehyde, and the mixture is stirred in a closed manner at 85°C for 2 hours, filtered, washed with water, and the filter cake is dried at 70°C for 24 hours to obtain modified diethyl aluminum hypophosphite.
[0022] Preferably, the high molecular polymer is obtained by polymerizing monomers under the action of an initiator, and the raw materials for its preparation include, by weight: 30-120 parts of soft monomers, 12-50 parts of hard monomers, 2-8 parts of functional monomers, 80-320 parts of a second solvent, and 0.6-3 parts of an initiator;
[0023] The soft monomer is one or more of ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate;
[0024] The hard monomer is one or more of acrylonitrile, vinyl acetate, acrylamide, styrene, methyl methacrylate, and methyl acrylate;
[0025] The functional monomer is one or more of methacrylic acid, acrylic acid, itaconic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, dimethylaminoethyl methacrylate, acrylamide, N-hydroxymethyl acrylamide, glycidyl methacrylate, and maleic anhydride;
[0026] The initiator is one or more of dibenzoyl peroxide, azobisisobutyronitrile, 2-methyl-2-n-butyltellurium-propionic acid, (methyltellurium-methyl)benzene, 1-chloro-4-(methyltellurium-methyl)benzene, 1-hydroxy-4-(methyltellurium-methyl)benzene, 1-phenoxycarboxyl-4-(2-methyltellurium-propyl)benzene, dimethyl ditellurium compounds, and diethyl ditellurium compounds;
[0027] The second solvent is one or more of toluene, ethyl acetate and butanone.
[0028] Preferably, the high molecular weight polymer is prepared by the following method:
[0029] In an atmosphere of nitrogen protection, the soft monomer, the hard monomer, the functional monomer and the second solvent are mixed, stirred evenly at room temperature, and then part of the initiator is added, the temperature is raised to 60-70°C, and the reaction is stirred for 3-12 hours; the remaining part of the initiator is added, the temperature is raised to 80-87°C, the reaction is performed for 1-4 hours, and the second solvent is added for dilution to obtain the high molecular polymer; the weight average molecular weight of the high molecular polymer ranges from 300,000 to 800,000, and the molecular weight distribution is between 3.0 and 5.0.
[0030] Preferably, the tackifying resin is selected from one or more of rosin resin, modified rosin resin, terpene resin and its derivatives, phenolic resin, and petroleum resin;
[0031] The curing agent is selected from one or more of isocyanates, epoxies, metal salts, and nitrogen pyridines;
[0032] The first solvent is one or more of toluene, ethyl acetate and butanone.
[0033] A second aspect of the present invention provides a method for preparing the high performance flame retardant adhesive as described above, comprising the following steps:
[0034] The tackifier resin is preliminarily dissolved in the first solvent, then mixed evenly with the high molecular polymer, a high-efficiency flame retardant is added under stirring, stirred, a curing agent is added and stirred evenly, and finally the first solvent is added for dilution to obtain the high-performance flame retardant adhesive.
[0035] In a third aspect of the present invention, there is provided a flame retardant cotton paper double-sided tape, comprising a cotton paper substrate layer, two pressure-sensitive adhesive layers located on both sides of the cotton paper substrate layer, and a release layer located outside the pressure-sensitive adhesive layer, wherein the flame retardant cotton paper double-sided tape is prepared by the following method:
[0036] The high-performance flame-retardant adhesive as described above is uniformly coated on the surfaces of the two release layers, and after drying and curing, the pressure-sensitive adhesive layers formed on the two release layers are respectively bonded to the two sides of the cotton paper substrate layer to obtain the flame-retardant cotton paper double-sided tape.
[0037] The beneficial effects of the present invention are:
[0038] The present invention provides a high-performance flame-retardant adhesive, a preparation method thereof and a flame-retardant cotton paper double-sided tape. The flame-retardant cotton paper double-sided tape provided by the present invention has good initial adhesion performance, high peeling force, high holding force and good flame-retardant performance; specifically, in some preferred embodiments, the following indicators can be achieved: the initial adhesion performance of the polyurethane foam material can reach the level of tearing the foam after bonding; the PP material has good adhesion performance, the initial adhesion performance reaches more than 20N / inch, and the peeling force reaches more than 15N / inch; in terms of holding force performance, it can reach the condition of 60℃*95%, and the 0.5kg weight can be hung without falling; in terms of flame-retardant performance, the tape body can reach the level of VTM-0, and in addition, after bonding the Velcro plastic of PP material, the horizontal combustion performance of the whole material can reach the level that the flame is extinguished before reaching the first marking line. While maintaining good flame-retardant performance, the flame-retardant cotton paper tape also has good adhesion performance to some difficult-to-bond materials, such as foam, PP sheet, etc., and has good practicality for bonding various automotive interior materials. The product of the present invention has broad market application prospects. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0040] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0041] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0042] The present invention provides a high-performance flame-retardant adhesive, comprising the following raw material components in parts by weight: 100 parts of a high molecular polymer, 40 to 80 parts by weight of a high-efficiency flame retardant, 5 to 50 parts by weight of a tackifying resin, 1 to 7 parts of a curing agent, and 60 to 100 parts by weight of a first solvent;
[0043] Wherein, the high-efficiency flame retardant is modified ammonium polyphosphate or modified diethyl aluminum hypophosphite.
[0044] High molecular polymers are usually obtained by polymerizing various acrylic monomers in a certain proportion in an organic solvent by free radical polymerization. Among them, various acrylic monomers can be roughly divided into hard monomers, soft monomers and functional monomers. In order to make the final pressure-sensitive adhesive have good comprehensive properties such as initial adhesion, peeling force and cohesion, there are certain requirements for the type and proportion of acrylic monomers selected for the preparation of high molecules. In addition, there are certain requirements for the weight average molecular weight of the prepared high molecular polymer. From the results, the weight average molecular weight range of the high molecular polymer is preferably 300,000 to 800,000, and the molecular weight distribution is between 3.0 and 5.0. When the weight-average molecular weight is too low, the glue molecular chain is too short, and the cohesive performance of the pressure-sensitive adhesive prepared using such a polymer is too low, resulting in poor heat resistance and shear resistance of the tape, which is not suitable for the purpose of the pressure-sensitive adhesive tape of the invention; when the weight-average molecular weight is too high, the cohesive performance of the glue will be significantly improved, but from the perspective of the wetting of the pressure-sensitive adhesive, the wetting performance of the tape for the adhered object will deteriorate, especially for some low surface energy and rough adhered objects, the initial bonding performance of the tape will deteriorate, which is not conducive to the processing and use of the tape. Similarly, when the molecular weight distribution is too wide, the cohesive performance of the glue is too low; when the molecular weight distribution is too narrow, the initial bonding performance of the glue will be affected. Through continuous experimental exploration, the present invention preferably has a molecular weight distribution range of 3.0 to 5.0.
[0045] In a preferred embodiment, the high molecular polymer is obtained by polymerizing monomers under the action of an initiator, and its preparation raw materials include, by weight: 30-120 parts of soft monomers, 12-50 parts of hard monomers, 2-8 parts of functional monomers, 80-320 parts of a second solvent, and 0.6-3 parts of an initiator.
[0046] In a preferred embodiment, the soft monomer is one or more of ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate.
[0047] In a preferred embodiment, the hard monomer is one or more of acrylonitrile, vinyl acetate, acrylamide, styrene, methyl methacrylate, and methyl acrylate.
[0048] In a preferred embodiment, the functional monomer is one or more of methacrylic acid, acrylic acid, itaconic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, dimethylaminoethyl methacrylate, acrylamide, N-hydroxymethyl acrylamide, glycidyl methacrylate, and maleic anhydride.
[0049] The initiator can be a polymerization initiator such as a peroxide compound, an azo compound, or an organic tellurium compound. In a preferred embodiment, the initiator is one or more of dibenzoyl peroxide, azobisisobutyronitrile, 2-methyl-2-n-butyltellurium-propionic acid, (methyltellurium-methyl) benzene, 1-chloro-4-(methyltellurium-methyl) benzene, 1-hydroxy-4-(methyltellurium-methyl) benzene, 1-phenoxycarboxyl-4-(2-methyltellurium-propyl) benzene, dimethyl ditellurium compounds, and diethyl ditellurium compounds. More preferably, it is a mixed system of an organic tellurium compound and a peroxide compound or an azo compound. By using a mixed system of an organic tellurium compound and a peroxide or an azo compound, a functional monomer having a polar functional group such as a hydroxyl group or a carboxyl group can be polymerized at a low active species concentration where all polymer chains are equally diffused, and a copolymer having a uniform molecular weight and composition is obtained, thereby achieving precise and controllable polymerization.
[0050] In a preferred embodiment, the second solvent is one or more of toluene, ethyl acetate, and butanone.
[0051] In a preferred embodiment, the high molecular weight polymer is prepared by the following method:
[0052] In an atmosphere of nitrogen protection, the soft monomer, the hard monomer, the functional monomer and the second solvent are mixed, stirred evenly at room temperature, and then part of the initiator is added, the temperature is raised to 60-70°C, and the reaction is stirred for 3-12 hours; the remaining part of the initiator is added, the temperature is raised to 80-87°C, the reaction is performed for 1-4 hours, and the second solvent is added for dilution to obtain a high molecular polymer; the weight average molecular weight of the high molecular polymer ranges from 300,000 to 800,000, and the molecular weight distribution is between 3.0 and 5.0.
[0053] Flame retardants can usually be divided into halogen-containing flame retardants, inorganic flame retardants, phosphorus-containing flame retardants, silicon-containing flame retardants, nitrogen-containing flame retardants, carbon-containing flame retardants, etc., among which, from the perspective of environmental protection, the current use of halogen-containing flame retardants has begun to receive more and more restrictions; inorganic flame retardants, such as aluminum hydroxide and magnesium hydroxide, achieve the purpose of flame retardancy by releasing water vapor under high-temperature thermal decomposition conditions to dilute the oxygen concentration in the air and reduce the temperature of the surface of the combustible. However, in order to achieve a better flame retardant effect, it is usually necessary to add a larger amount. On the other hand, adding too much flame retardant will reduce the bonding properties of the pressure-sensitive adhesive itself, such as retention, peeling force, initial adhesion, etc.; the flame retardant effect of silicon-containing flame retardants is general, and they are used in pressure-sensitive adhesives. There are not many usage scenarios; phosphorus-containing flame retardants and nitrogen-containing flame retardants are currently attracting more and more attention from professionals due to their excellent flame retardant efficiency. In terms of composition, this type of flame retardant can be further divided into organic flame retardants and inorganic flame retardants. Organic flame retardants can be triphenyl phosphate, tricresyl phosphate, tri(xylene) phosphate, hexaphenoxycyclotriphosphazene, melamine, etc., and inorganic flame retardants can be ammonium polyphosphate, pentaerythritol, diethyl aluminum hypophosphite, phosphate ester, polyphosphate ester, red phosphorus, melamine phosphate, melamine pyrophosphate, melamine polyphosphate, melamine cyanurate, etc. The above flame retardants can be used alone or in combination. Since the pressure-sensitive adhesive system is flammable, in order to achieve a better flame retardant effect, the above flame retardants still face the problem of large addition amount.
[0054] The high-efficiency flame retardant provided by the present invention is a phosphorus-nitrogen type flame retardant that has been surface-modified. The surface improvement can be performed by using surfactants, coupling agents, surface grafting, or microencapsulation. However, the particle size will increase after microencapsulation. Since the thickness of the flame-retardant pressure-sensitive adhesive is generally about tens of microns, it is not conducive to the dispersion and coating of the pressure-sensitive adhesive system, especially for thin layers of flame-retardant pressure-sensitive adhesives. Surfactant modification usually requires first using a solvent, such as a linear chlorinated alkane, aromatic hydrocarbon or chlorinated aromatic hydrocarbon, to dissolve the surfactant. Then the surface of the flame retardant is modified by adsorbing a surfactant on the surface of the flame retardant, and then removing the excess solution. The modification effect of this method is limited, and since some toxic solvents are required in the treatment process, it is less used now. Therefore, the present invention preferably uses a type of phosphorus-nitrogen type flame retardant that has been surface-modified by surface grafting treatment, wherein the surface modification material can be melamine formaldehyde resin, melamine, etc., preferably melamine formaldehyde resin, flame retardant phosphate, ammonium polyphosphate, diethyl aluminum hypophosphite, etc., preferably ammonium polyphosphate, diethyl aluminum hypophosphite.
[0055] The present invention also provides a method for modifying the surface of a flame retardant, first activating the flame retardant at high temperature, then grafting with an auxiliary flame retardant as a surface modification material, and finally crosslinking with formaldehyde to obtain a modified high-efficiency flame retardant. Specifically, the present invention preferably uses two high-efficiency flame retardants: modified ammonium polyphosphate or modified diethyl aluminum hypophosphite, and the preparation method thereof is as follows.
[0056] Wherein, the modified ammonium polyphosphate is prepared by the following method:
[0057] 1-1) 50-200 g of ammonium polyphosphate passed through a 200 mesh sieve is heated and stirred at 220-260° C. for 20-80 min for activation, and then 5-20 g of melamine formaldehyde resin is added, and the temperature is maintained and stirred for 1-4 hours in a closed environment to obtain ammonium polyphosphate grafted with melamine formaldehyde resin;
[0058] 1-2) The melamine formaldehyde resin grafted ammonium polyphosphate prepared in step 1-1) is mixed with a methanol aqueous solution with a mass fraction of 6-24% in a mass ratio of 0.5-2:1-4, and then 20-50wt% of formalin solution is added in a ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde molar ratio = 0.5-2:1-4, and the mixture is stirred in a closed manner at 70-95° C. for 1-4 hours, filtered, washed with water, and the obtained filter cake is dried to obtain modified ammonium polyphosphate.
[0059] Wherein, modified diethyl aluminum hypophosphite is prepared by the following method:
[0060] 1-1) 50-200 g of diethyl aluminum hypophosphite passed through a 200 mesh sieve is heated and stirred at 220-260° C. for 20-80 min for activation, and then 5-20 g of melamine formaldehyde resin is added, and the temperature is maintained and stirred for 1-4 hours in a closed environment to obtain diethyl aluminum hypophosphite grafted with melamine formaldehyde resin;
[0061] 1-2) The melamine formaldehyde resin grafted diethyl aluminum hypophosphite prepared in step 1-1) is mixed with a methanol aqueous solution with a mass fraction of 6-24% in a mass ratio of 0.5-2:1-4, and then 20-50wt% of formalin solution is added in a ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde molar ratio = 0.5-2:1-4, and the mixture is stirred in a closed manner at 70-95° C. for 1-4 hours, filtered, washed with water, and the obtained filter cake is dried to obtain modified diethyl aluminum hypophosphite.
[0062] In order to obtain a good flame retardant effect, the high-efficiency flame retardant can be properly ground before use to control the particle size within a certain range to facilitate its dispersion in the glue system. After adding the high-efficiency flame retardant, try to maintain a high-speed dispersion state to ensure that the flame retardant particles can be evenly dispersed in the glue system to prevent agglomeration between the flame retardant particles, resulting in a decrease in the appearance and performance of the tape. In addition, the high-efficiency flame retardant and the high molecular polymer or the glue without the addition of a curing agent can also be processed by a grinding process to obtain a flame retardant glue with a stable particle size and uniform dispersion. Among them, the grinding method can be one or more of a variety of methods such as three-roller grinding, ball milling, sand milling, planetary dispersion, etc., and the present invention does not make any special restrictions on it.
[0063] In a preferred embodiment, the tackifying resin is selected from one or more of rosin resins, modified rosin resins, terpene resins and their derivatives, phenolic resins, and petroleum resins. The present invention is more preferably modified rosin and terpene phenolic resins, which can be obtained in a commercially available manner. The addition ratio of the tackifying resin is 5 to 50 parts by weight. When a compounding method of multiple resins is adopted, the total amount of added resin should not exceed 50 parts by weight. When the resin content is higher than 50 parts by weight, the pressure-sensitive adhesive will be hard as a whole, and it will not be able to exert good wetting properties, and thus it will not be able to exert good bonding properties; when the resin content is lower than 5 parts by weight, the molecular chain segments of the polymer cannot be fully expanded due to the lack of tackifying resin, and it is also impossible to exert good wetting properties, and thus it is impossible to exert good bonding properties.
[0064] In a preferred embodiment, the curing agent is selected from one or more of isocyanates, epoxies, metal salts, and nitrogen pyridines; the present invention does not specifically limit it, but from the perspective of high temperature resistance and high cohesion, isocyanate and epoxy curing agents are preferred. These curing agents can be obtained through common commercial methods.
[0065] In a preferred embodiment, the first solvent is one or more of toluene, ethyl acetate, and butanone. The present invention does not specifically limit the solvent used, but ethyl acetate is preferred from the perspectives of odor and environmental protection.
[0066] In some optional embodiments, the formula of the high-performance flame-retardant adhesive may also include a certain amount of additives, which may be some color pastes, surfactants, antistatic agents, coupling agents, etc., and may be added specifically according to actual application requirements. The present invention does not impose any special limitation on them.
[0067] The present invention also provides a method for preparing the high-performance flame-retardant adhesive as above, comprising the following steps:
[0068] The tackifying resin is preliminarily dissolved with the first solvent, and then mixed evenly with the high molecular polymer, a high-efficiency flame retardant is added under stirring, and the curing agent is added and stirred evenly, and finally the first solvent is added for dilution to obtain a high-performance flame retardant adhesive.
[0069] The present invention also provides a flame retardant cotton paper double-sided tape, comprising a cotton paper substrate layer, two pressure-sensitive adhesive layers located on both sides of the cotton paper substrate layer, and a release layer located outside the pressure-sensitive adhesive layer. The flame retardant cotton paper double-sided tape is prepared by the following method:
[0070] The high-performance flame-retardant adhesive as above is evenly coated on the surfaces of the two release layers respectively. After drying and curing, the pressure-sensitive adhesive layers formed on the two release layers are respectively bonded to the two sides of the cotton paper substrate layer to obtain a flame-retardant cotton paper double-sided tape.
[0071] The flame-retardant cotton paper double-sided tape has good initial adhesion, high peeling force, high holding force and good flame retardant properties. Specifically, the initial adhesion of polyurethane foam materials can reach the level of tearing the foam after bonding; it has good adhesion to PP materials, with initial adhesion reaching more than 20N / inch and peeling force reaching more than 15N / inch; in terms of holding force, it can reach the level of hanging a 0.5kg weight without falling under the condition of 60℃*95%; in terms of flame retardant properties, the tape body can reach the level of VTM-0. In addition, after bonding the Velcro plastic made of PP material, the overall horizontal combustion performance of the material can reach the level where the flame is extinguished before reaching the first mark.
[0072] The release layer can be a commonly used silicone release material in the industry, and its function is to facilitate operations such as winding, unwinding, and die-cutting. The material of the release material can be plastic film, paper, etc. The present invention does not specifically limit its type and thickness. However, in order to better achieve the effect of winding and unwinding, a release material with a release force in the range of 5 to 40 gf / inch is preferred. Too small a release force will result in poor adhesion to the pressure-sensitive adhesive layer, and too large a release force will result in deformation of the tape sample during unwinding and peeling, making it difficult to peel off, etc.
[0073] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0074] Example 1
[0075] A flame retardant cotton paper double-sided tape comprises a cotton paper substrate layer, two pressure-sensitive adhesive layers located on both sides of the cotton paper substrate layer, and a release layer located outside the pressure-sensitive adhesive layer. The flame retardant cotton paper double-sided tape is prepared by the following method:
[0076] S1. Preparation of high molecular polymer:
[0077] In a nitrogen atmosphere, 150 parts by weight of ethyl acetate, 60 parts by weight of butyl acrylate, 25 parts by weight of hard monomer methyl acrylate and 4 parts by weight of acrylic acid were added to a four-necked reactor and stirred at room temperature. Under the nitrogen atmosphere, 0.8 parts by weight of dibenzoyl peroxide was dissolved in 5 parts by weight of ethyl acetate and added to the four-necked reactor. The temperature was heated to 65° C. to initiate polymerization. Stirring and temperature control were continued. After reacting for 6 hours, 0.5 parts by weight of dibenzoyl peroxide diluted with 5 parts by weight of ethyl acetate was added. The temperature was further raised to 85° C., and a certain amount of ethyl acetate was added after the reaction was kept warm for 2 hours to obtain a free radical polymerization acrylic polymer solution with a solid content of 40%. The free radical polymerization polymer solution was tested by gel permeation chromatography. The molecular weight of the free radical polymerization polymer was 650,000 and the molecular weight distribution was 4.09.
[0078] S2. Preparation of high-efficiency flame retardant (modified ammonium polyphosphate):
[0079] 1-1) Add 100 g of ammonium polyphosphate (AMP) sieved through a 200-mesh sieve to a glass reactor with a self-stirring device, heat and stir in an oil bath at 240° C. for activation for 40 minutes, add 10 g of melamine formaldehyde resin, continue heating and stirring in a closed environment for 2 hours, and obtain melamine formaldehyde resin-grafted AMP;
[0080] 1-2) The melamine formaldehyde resin grafted ammonium polyphosphate prepared in step 1-1) is mixed with a 12% methanol aqueous solution in a mass ratio of 1:2, and then a 37wt% formalin solution is added in a ratio of a molar ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde = 1:2, and the mixture is stirred in a closed manner at 85°C for 2 hours, filtered, washed with water, and the filter cake is dried at 70°C for 24 hours to obtain modified ammonium polyphosphate.
[0081] S3. Preparation of high performance flame retardant adhesive:
[0082] Take 100 parts by weight of the above-mentioned high molecular polymer, add 25 parts by weight of KB-120 resin (Guangzhou Kemao Chemical Co., Ltd.) and 10 parts by weight of TP-2040 resin (Covestro). Before adding the resin, a solvent can be used to dissolve it. While maintaining the stirring state, add 60 parts by weight of modified ammonium polyphosphate, a high-efficiency flame retardant (60 parts by weight of modified ammonium polyphosphate are pre-mixed with 60 parts by weight of ethyl acetate for uniform wetting), and use a high-speed dispersing device with a stator and rotor to disperse for 20 minutes. Finally, add 3 parts by weight of L-75 resin (curing agent) (Covestro) (pre-diluted with 5 parts by weight of ethyl acetate and then added), stir evenly, and dilute with 20 parts by weight of ethyl acetate solvent to obtain a high-performance flame retardant adhesive;
[0083] S4. Preparation of flame retardant cotton paper double-sided tape:
[0084] The high-performance flame-retardant adhesive was evenly coated on the surfaces of the two release layers by blade coating, dried in an oven at 120°C for 2 minutes. After curing, the 70-micron thick pressure-sensitive adhesive layer formed on the two release layers was respectively bonded to the two sides of the cotton paper substrate layer with a weight of 9 grams per square meter to obtain a flame-retardant cotton paper double-sided tape.
[0085] Example 2
[0086] A flame retardant cotton paper double-sided tape comprises a cotton paper substrate layer, two pressure-sensitive adhesive layers located on both sides of the cotton paper substrate layer, and a release layer located outside the pressure-sensitive adhesive layer. The flame retardant cotton paper double-sided tape is prepared by the following method:
[0087] S1. Preparation of high molecular polymer, same as in Example 1:
[0088] S2. Preparation of high-efficiency flame retardant (modified diethyl aluminum hypophosphite):
[0089] 1-1) Add 100 g of diethylaluminum hypophosphite passed through a 200-mesh sieve to a glass reactor with a self-stirring device, heat and stir in an oil bath at 240° C. for activation for 40 minutes, add 10 g of melamine formaldehyde resin, continue heating and stirring in a closed environment for 2 hours, and obtain diethylaluminum hypophosphite grafted with melamine formaldehyde resin;
[0090] 1-2) The melamine formaldehyde resin grafted diethyl aluminum hypophosphite prepared in step 1-1) is mixed with a 12% methanol aqueous solution in a mass ratio of 1:2, and then a 37wt% formalin solution is added in a ratio of 1:2 of the molar ratio of ammonium polyphosphate grafted with melamine formaldehyde resin: formaldehyde, and the mixture is stirred in a closed manner at 85°C for 2 hours, filtered, washed with water, and the filter cake is dried at 70°C for 24 hours to obtain modified diethyl aluminum hypophosphite.
[0091] S3. Preparation of high performance flame retardant adhesive:
[0092] Take 100 parts by weight of the above-mentioned high molecular polymer, add 25 parts by weight of KB-120 resin (Guangzhou Kemao Chemical Co., Ltd.) and 10 parts by weight of TP-2040 resin (Kateng Company). Before adding the resin, a solvent can be used to dissolve it. Keep stirring, add 60 parts by weight of modified diethyl aluminum hypophosphite (modified diethyl aluminum hypophosphite is pre-mixed with 60 parts by weight of ethyl acetate for wetting), and use a high-speed dispersing device with a stator and rotor to disperse for 20 minutes. Finally, add 3 parts by weight of L-75 resin (curing agent) (Covestro Company) (pre-diluted with 5 parts by weight of ethyl acetate and then added), stir evenly, and dilute with 20 parts by weight of ethyl acetate solvent to obtain a high-performance flame retardant adhesive;
[0093] S4. Preparation of flame retardant cotton paper double-sided tape:
[0094] The high-performance flame-retardant adhesive was evenly coated on the surfaces of the two release layers by blade coating, dried in an oven at 120°C for 2 minutes. After curing, the 70-micron thick pressure-sensitive adhesive layer formed on the two release layers was respectively bonded to the two sides of the cotton paper substrate layer with a weight of 9 grams per square meter to obtain a flame-retardant cotton paper double-sided tape.
[0095] Example 3
[0096] A flame retardant cotton paper double-sided tape comprises a cotton paper substrate layer, two pressure-sensitive adhesive layers located on both sides of the cotton paper substrate layer, and a release layer located outside the pressure-sensitive adhesive layer. The flame retardant cotton paper double-sided tape is prepared by the following method:
[0097] S1, preparing a high molecular polymer, the same as in Example 1;
[0098] S2, preparing a high-efficiency flame retardant (modified diethyl aluminum hypophosphite), the same as in Example 2;
[0099] S3. Preparation of high performance flame retardant adhesive:
[0100] Take 100 parts by weight of the above-mentioned high molecular polymer, add 25 parts by weight of KB-120 resin (Guangzhou Kemao Chemical Co., Ltd.) and 10 parts by weight of TP-2019 resin (Kateng Company). Before adding the resin, a solvent can be used to dissolve it. Keep stirring, add 60 parts by weight of modified diethyl aluminum hypophosphite (modified diethyl aluminum hypophosphite is pre-mixed with 60 parts by weight of ethyl acetate for wetting), and use a high-speed dispersing device with a stator and rotor to disperse for 20 minutes. Finally, add 3 parts by weight of L-75 resin (curing agent) (Covestro Company) (pre-diluted with 5 parts by weight of ethyl acetate and then added), stir evenly, and dilute with 20 parts by weight of ethyl acetate solvent to obtain a high-performance flame retardant adhesive;
[0101] S4. Preparation of flame retardant cotton paper double-sided tape:
[0102] The high-performance flame-retardant adhesive was evenly coated on the surfaces of the two release layers by blade coating, dried in an oven at 120°C for 2 minutes. After curing, the 70-micron thick pressure-sensitive adhesive layer formed on the two release layers was respectively bonded to the two sides of the cotton paper substrate layer with a weight of 9 grams per square meter to obtain a flame-retardant cotton paper double-sided tape.
[0103] Example 4
[0104] A flame retardant cotton paper double-sided tape comprises a cotton paper substrate layer, two pressure-sensitive adhesive layers located on both sides of the cotton paper substrate layer, and a release layer located outside the pressure-sensitive adhesive layer. The flame retardant cotton paper double-sided tape is prepared by the following method:
[0105] S1, preparing a high molecular polymer, the same as in Example 1;
[0106] S2, preparing a high-efficiency flame retardant (modified ammonium polyphosphate), the same as in Example 1;
[0107] S3. Preparation of high performance flame retardant adhesive:
[0108] Take 100 parts by weight of the above-mentioned high molecular polymer, add 25 parts by weight of KB-120 resin (Guangzhou Kemao Chemical Co., Ltd.) and 10 parts by weight of TP-2019 resin (Kateng Company). Before adding the resin, a solvent can be used to dissolve it. Keep stirring, add 60 parts by weight of modified diethyl aluminum hypophosphite (modified diethyl aluminum hypophosphite is pre-mixed with 60 parts by weight of ethyl acetate for wetting), and use a high-speed dispersing device with a stator and rotor to disperse for 20 minutes. Finally, add 3 parts by weight of L-75 resin (curing agent) (Covestro Company) (pre-diluted with 5 parts by weight of ethyl acetate and then added), stir evenly, and dilute with 20 parts by weight of ethyl acetate solvent to obtain a high-performance flame retardant adhesive;
[0109] S4. Preparation of flame retardant cotton paper double-sided tape:
[0110] The high-performance flame-retardant adhesive was evenly coated on the surfaces of the two release layers by blade coating, dried in an oven at 120°C for 2 minutes. After curing, the 70-micron thick pressure-sensitive adhesive layer formed on the two release layers was respectively bonded to the two sides of the cotton paper substrate layer with a weight of 9 grams per square meter to obtain a flame-retardant cotton paper double-sided tape.
[0111] Comparative Example 1
[0112] S1. Preparation of flame retardant adhesive:
[0113] Commercially available glue PS-8231 (Kunshan Shimei New Material Technology Co., Ltd.) was used. While maintaining stirring, 60 parts by weight of flame retardant diethyl aluminum hypophosphite (diethyl aluminum hypophosphite was pre-mixed with 60 parts by weight of ethyl acetate for wetting) was added, and a high-speed dispersing device with a stator and rotor was used for dispersion for 20 minutes. Finally, 3 parts by weight of L-75 resin (curing agent) (Covestro) was added (pre-diluted with 5 parts by weight of ethyl acetate and then added), stirred evenly, and diluted with 20 parts by weight of ethyl acetate solvent to obtain a flame retardant adhesive;
[0114] S2. Preparation of flame retardant cotton paper double-sided tape:
[0115] The flame retardant adhesive was evenly coated on the surfaces of the two release layers by blade coating and dried in an oven at 120°C for 2 minutes. After curing, the 70-micron thick pressure-sensitive adhesive layer formed on the two release layers was respectively bonded to the two sides of the cotton paper substrate layer with a weight of 9 grams per square meter to obtain a flame retardant cotton paper double-sided tape.
[0116] Comparative Example 2
[0117] S1. Preparation of flame retardant adhesive:
[0118] Commercially available glue PS-8231 (Kunshan Shimei New Material Technology Co., Ltd.) was used. While maintaining stirring, 60 parts by weight of flame retardant ammonium polyphosphate (ammonium polyphosphate was pre-mixed with 60 parts by weight of ethyl acetate for wetting) was added, and a high-speed dispersing device with a stator and rotor was used for dispersion for 20 minutes. Finally, 3 parts by weight of L-75 resin (curing agent) (Covestro) was added (pre-diluted with 5 parts by weight of ethyl acetate and then added), stirred evenly, and diluted with 20 parts by weight of ethyl acetate solvent to obtain a flame retardant adhesive;
[0119] S2. Preparation of flame retardant cotton paper double-sided tape:
[0120] The flame retardant adhesive was evenly coated on the surfaces of the two release layers by blade coating and dried in an oven at 120°C for 2 minutes. After curing, the 70-micron thick pressure-sensitive adhesive layer formed on the two release layers was respectively bonded to the two sides of the cotton paper substrate layer with a weight of 9 grams per square meter to obtain a flame retardant cotton paper double-sided tape.
[0121] Comparative Example 3
[0122] This example is basically the same as Example 1, except that aluminum hydroxide is used instead of the modified ammonium polyphosphate in Example 1.
[0123] The flame retardant cotton paper double-sided tapes prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to the following performance tests:
[0124] 1. Test of molecular weight and molecular weight distribution
[0125] The obtained solution containing acrylic polymer was diluted 50 times with tetrahydrofuran, and the obtained dilution was filtered with a filter (polytetrafluoroethylene material, 0.2 μm pore size). The obtained filtrate was tested by gel permeation chromatography (Waters Company), wherein a GPC KF-806L (Showa Denko Co., Ltd.) chromatographic column was used and a differential refractometer was used as a detector. The test conditions were set to a flow rate of 1 ml / min and a column temperature of 40°C, and the polystyrene-equivalent molecular weight of the acrylic polymer was measured to obtain the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn).
[0126] 2. Initial adhesion test of PU foam
[0127] The sample is cut into 50m width and 150mm length. The tape is attached to the surface of the PU foam. After being pressed back and forth by a 2kg roller, it is placed at 23℃ and 50%RH for 1 hour. It is then placed in a 50℃ oven for 3 minutes. It is manually torn and peeled in the oven. The damage morphology of the foam is observed. If the foam is torn, it is considered qualified.
[0128] 3. Initial adhesion test
[0129] The test was conducted according to ASTM D6195. The sample was cut into 25 mm width and 150 mm length. After being placed at 23°C and 50% RH for at least 2 hours, the sample was rolled into an ellipse with the adhesive surface facing outward and fixed with a clamp. A peel force measuring device (tensile testing machine, Shimadzu Corporation) was used to adjust the position of the adhesive surface to completely contact the test PP plastic plate. The test was conducted at a peel speed of 300 mm / min, and the average value of N=3 was taken as the measured value.
[0130] 4. Peel force test
[0131] The measurement was carried out according to the ASTM D3330 method. The sample was cut into 25 mm width and 150 mm length. After being placed at 23°C and 50% RH for at least 2 hours, it was attached to a cleaned PP plastic plate and pressed back and forth once with a 2 kg pressing roller. The sample was peeled off at a peeling angle of 180° and a peeling speed of 300 mm / min using a peeling force measuring device (tensile testing machine, Shimadzu Corporation). The 180° peeling force was tested, and the average value of N=3 was taken as the measured value.
[0132] 5. Test of holding power
[0133] The test was carried out according to the ASTM D3654 method. The sample was cut into 25mm width and 150mm length. After being placed at 23℃ and 50%RH for at least 2 hours, it was attached to the cleaned glass. A 2kg pressing roller was used to press back and forth once, keeping the attached area at 25mm*25mm. A 0.5kg weight was hung and the sample was kept in an oven at 60℃*95%RH for 1 day to observe whether the tape was displaced or fell off.
[0134] 6. Horizontal flame retardant performance test
[0135] The sample was cut into 50m width and 150mm length. The tape was attached to the surface of the PP Velcro and pressed back and forth with a 2kg roller. After being placed for 1 hour under the conditions of temperature 23℃ and humidity 50%RH, the flame retardancy test was carried out in a horizontal flame retardant combustion test box. According to the national standard GB 8410-2006 method, the burning distance and the final burning result were recorded.
[0136] The burning speed is calculated as follows: V = 60*(L / T)
[0137] V: burning speed, in millimeters per minute;
[0138] L: burning distance, in millimeters;
[0139] T: time used to burn the distance L, in seconds;
[0140] The burning rate is the maximum value of the burning rates of 5 or more samples tested as the experimental result.
[0141] If the sample is exposed to the flame for 15s and the sample still does not burn after the fire source is extinguished, or the sample can burn but the flame extinguishes before reaching the first measuring mark and there is no burning distance to be calculated, it is considered to meet the burning speed requirements and the results are recorded as A-0mm / min; if the flame extinguishes itself within 60s from the start of the test timing and the burning distance is not greater than 50mm, it is also considered to meet the burning speed requirements and the result is recorded as B; if the flame extinguishes between the two measuring marks from the start of the test timing, it is a self-extinguishing sample and does not meet the requirement of result B, then the burning speed is calculated and the result is recorded as C, and the actual measured value of the burning speed is mm / min; if the flame burns to the second mark from the start of the test timing, or if the sample burns slowly for a long time from the start of the timing, the test can be terminated when the test timing is 20min, and the burning time and burning distance are recorded, and the burning speed is calculated as required, and the result is recorded as D, and the actual measured value of the burning speed is mm / min; if the sample has burned and reached the first mark within 15s of the flame ignition, it is considered that the sample does not meet the burning speed requirements and the result is recorded as E.
[0142] 7. Vertical flame retardant performance test
[0143] The prepared sample size is 200mm long and 50mm wide, the machine coating direction is the length direction, the number of samples is 5 pieces, the first group: placed in an environment of 23±2℃, RH50±5% for more than 40h, the second group: treated in an oven at 70±2℃ for 168h, the flame height is 20mm, the first flame application time is 3s, and the afterflame time t1 is recorded, the second flame application time is 3s, and the afterflame time t2 and afterburning time t3 are recorded. According to the UL94 test standard, the final result is recorded as VTM-0, VTM-1, VTM-2 or non-flame retardant.
[0144] The test results are shown in Table 1 below:
[0145] Table 1
[0146]
[0147]
[0148] According to the test results in Table 1, it can be seen that the flame-retardant cotton paper double-sided tape provided by Examples 1-4 of the present invention has good initial adhesion performance, high peeling force, high holding force and good flame retardant performance. Specifically, the initial adhesion performance of the polyurethane foam material can reach the level of tearing the foam after bonding; it has good adhesion performance for PP materials, the initial adhesion performance reaches more than 20N / inch, and the peeling force reaches more than 15N / inch; in terms of holding performance, it can reach 60℃*95% conditions, and a 0.5kg weight can be hung without falling; in terms of flame retardant performance, the tape body can reach the level of VTM-0. In addition, after bonding the Velcro plastic made of PP material, the overall horizontal combustion performance of the material can reach the level where the flame is extinguished before reaching the first marking line. While maintaining good flame retardant performance, the flame-retardant cotton paper tape also has good adhesion performance for some difficult-to-bond materials, such as foam, PP sheet, etc., and has good practicality for bonding various automotive interior materials.
[0149] The comparison results between the comparative examples and the embodiments indicate that the flame retardant tissue paper tape prepared by the synergistic effect of the high-efficiency flame retardant and the adhesive provided by the present invention has good comprehensive properties such as initial adhesion, peeling force, holding force and flame retardancy.
[0150] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A high performance flame retardant adhesive, characterized in that: The invention comprises the following raw material components in parts by weight: 100 parts of high molecular polymer, 40 to 80 parts by weight of high efficiency flame retardant, 5 to 50 parts by weight of tackifying resin, 1 to 7 parts of curing agent, and 60 to 100 parts by weight of first solvent; Wherein, the high-efficiency flame retardant is modified ammonium polyphosphate or modified diethyl aluminum hypophosphite.
2. The high performance flame retardant adhesive according to claim 1, characterized in that: The modified ammonium polyphosphate is prepared by the following method: 1-1) 50-200 g of ammonium polyphosphate passed through a 200 mesh sieve is heated and stirred at 220-260° C. for 20-80 min for activation, and then 5-20 g of melamine formaldehyde resin is added, and the temperature is maintained and stirred for 1-4 hours in a closed environment to obtain ammonium polyphosphate grafted with melamine formaldehyde resin; 1-2) The melamine formaldehyde resin grafted ammonium polyphosphate prepared in step 1-1) is mixed with a methanol aqueous solution with a mass fraction of 6-24% in a mass ratio of 0.5-2:1-4, and then 20-50wt% of formalin solution is added in a ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde molar ratio = 0.5-2:1-4, and the mixture is stirred in a closed manner at 70-95° C. for 1-4 hours, filtered, washed with water, and the obtained filter cake is dried to obtain modified ammonium polyphosphate.
3. The high performance flame retardant adhesive according to claim 2, characterized in that: The modified ammonium polyphosphate is prepared by the following method: 1-1) 100 g of ammonium polyphosphate passed through a 200 mesh sieve was heated and stirred at 240° C. for 40 min for activation, and then 10 g of melamine formaldehyde resin was added, and the temperature was maintained and stirred for 2 hours in a closed environment to obtain ammonium polyphosphate grafted with melamine formaldehyde resin; 1-2) The melamine formaldehyde resin grafted ammonium polyphosphate prepared in step 1-1) is mixed with a 12% methanol aqueous solution in a mass ratio of 1:2, and then a 37wt% formalin solution is added in a ratio of a molar ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde = 1:2, and the mixture is stirred in a closed manner at 85°C for 2 hours, filtered, washed with water, and the filter cake is dried at 70°C for 24 hours to obtain modified ammonium polyphosphate.
4. The high performance flame retardant adhesive according to claim 1, characterized in that: The modified diethyl aluminum hypophosphite is prepared by the following method: 1-1) 50-200 g of diethyl aluminum hypophosphite passed through a 200 mesh sieve is heated and stirred at 220-260° C. for 20-80 min for activation, and then 5-20 g of melamine formaldehyde resin is added, and the temperature is maintained and stirred for 1-4 hours in a closed environment to obtain diethyl aluminum hypophosphite grafted with melamine formaldehyde resin; 1-2) The melamine formaldehyde resin grafted diethyl aluminum hypophosphite prepared in step 1-1) is mixed with a methanol aqueous solution with a mass fraction of 6-24% in a mass ratio of 0.5-2:1-4, and then 20-50wt% of formalin solution is added in a ratio of melamine formaldehyde resin grafted ammonium polyphosphate: formaldehyde molar ratio = 0.5-2:1-4, and the mixture is stirred in a closed manner at 70-95° C. for 1-4 hours, filtered, washed with water, and the obtained filter cake is dried to obtain modified diethyl aluminum hypophosphite.
5. The high performance flame retardant adhesive according to claim 4, characterized in that: The modified diethyl aluminum hypophosphite is prepared by the following method: 2-1) 100 g of diethylaluminum hypophosphite passed through a 200-mesh sieve was taken, heated and stirred at 240° C. for 40 min for activation, and then 10 g of melamine formaldehyde resin was added, and the temperature was maintained and stirred for 2 hours in a closed environment to obtain diethylaluminum hypophosphite grafted with melamine formaldehyde resin; 1-2) The melamine formaldehyde resin grafted diethyl aluminum hypophosphite prepared in step 1-1) is mixed with a 12% methanol aqueous solution in a mass ratio of 1:2, and then a 37wt% formalin solution is added in a ratio of 1:2 of the molar ratio of ammonium polyphosphate grafted with melamine formaldehyde resin: formaldehyde, and the mixture is stirred in a closed manner at 85°C for 2 hours, filtered, washed with water, and the filter cake is dried at 70°C for 24 hours to obtain modified diethyl aluminum hypophosphite.
6. The high performance flame retardant adhesive according to claim 1, characterized in that: The high molecular polymer is obtained by polymerizing monomers under the action of an initiator, and the raw materials for its preparation include, by weight: 30-120 parts of soft monomers, 12-50 parts of hard monomers, 2-8 parts of functional monomers, 80-320 parts of a second solvent, and 0.6-3 parts of an initiator; The soft monomer is one or more of ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate; The hard monomer is one or more of acrylonitrile, vinyl acetate, acrylamide, styrene, methyl methacrylate, and methyl acrylate; The functional monomer is one or more of methacrylic acid, acrylic acid, itaconic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, dimethylaminoethyl methacrylate, acrylamide, N-hydroxymethyl acrylamide, glycidyl methacrylate, and maleic anhydride; The initiator is one or more of dibenzoyl peroxide, azobisisobutyronitrile, 2-methyl-2-n-butyltellurium-propionic acid, (methyltellurium-methyl)benzene, 1-chloro-4-(methyltellurium-methyl)benzene, 1-hydroxy-4-(methyltellurium-methyl)benzene, 1-phenoxycarboxyl-4-(2-methyltellurium-propyl)benzene, dimethyl ditellurium compounds, and diethyl ditellurium compounds; The second solvent is one or more of toluene, ethyl acetate and butanone.
7. The high performance flame retardant adhesive according to claim 1, characterized in that: The high molecular weight polymer is prepared by the following method: In an atmosphere of nitrogen protection, the soft monomer, the hard monomer, the functional monomer and the second solvent are mixed, stirred evenly at room temperature, and then part of the initiator is added, the temperature is raised to 60-70°C, and the reaction is stirred for 3-12 hours; the remaining part of the initiator is added, the temperature is raised to 80-87°C, the reaction is performed for 1-4 hours, and the second solvent is added for dilution to obtain the high molecular polymer; the weight average molecular weight of the high molecular polymer ranges from 300,000 to 800,000, and the molecular weight distribution is between 3.0 and 5.
0.
8. The high performance flame retardant adhesive according to claim 6, characterized in that: The tackifying resin is selected from one or more of rosin resin, modified rosin resin, terpene resin and its derivatives, phenolic resin and petroleum resin; The curing agent is selected from one or more of isocyanates, epoxies, metal salts, and nitrogen pyridines; The first solvent is one or more of toluene, ethyl acetate and butanone.
9. A method for preparing a high-performance flame-retardant adhesive as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: The tackifier resin is preliminarily dissolved in the first solvent, then mixed evenly with the high molecular polymer, a high-efficiency flame retardant is added under stirring, stirred, a curing agent is added and stirred evenly, and finally the first solvent is added for dilution to obtain the high-performance flame retardant adhesive.
10. A flame retardant cotton paper double-sided tape, characterized in that: The flame retardant cotton paper double-sided tape comprises a cotton paper substrate layer, two pressure-sensitive adhesive layers located on both sides of the cotton paper substrate layer, and a release layer located outside the pressure-sensitive adhesive layer. The flame retardant cotton paper double-sided tape is prepared by the following method: The high-performance flame-retardant adhesive as described in any one of claims 1 to 8 is uniformly coated on the surfaces of the two release layers, and after drying and curing, the pressure-sensitive adhesive layers formed on the two release layers are respectively bonded to the two sides of the cotton paper substrate layer to obtain the flame-retardant cotton paper double-sided tape.
Citation Information
Patent Citations
Fire-retardant polyacrylacid ester adhesive and preparation thereof
CN101407707A
Preparation method of halogen-free environment-friendly flame-retardant acrylate pressure-sensitive adhesive
CN102719206A
Flame retardant epoxy resin adhesive and preparation method thereof
CN110305590A
Preparation method of low-VOC (volatile organic compound) halogen-free flame-retardant pressure-sensitive adhesive
CN114058297A
Cited By
Acrylate polymer emulsion, pressure-sensitive adhesive, tissue paper double-sided tape and application thereof
CN121181767A